Uncertainty, Financial Reporting Quality and Accounting Enforcement: Evidence from The European Union - Catalin Mos (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Question- What is the impact of uncertainty on the quality of financial reporting in the European Union and whether accounting enforcement is a critical factor? Motivation- The advances made by the European Union (EU) in the field of financial reporting have shown the commitment to improve its quality. However, uncertainty creates a difficult context for capital markets, investors, and management. Since financial reporting represents the primary source of information for investors, its quality under uncertainty is a key topic of research. Furthermore, considering the EU efforts to strengthen accounting enforcement, it is fundamental to investigate whether accounting enforcement acts as a moderating factor between uncertainty and financial reporting quality. Idea- Our study investigates the effects of uncertainty on the quality of financial reporting in the European Union and the role of accounting enforcement. Data- The sample consists of 35,489 firm-year observations from the 27 EU countries. The sample does not include firms from the finance industry, as they are subject to specific regulations and oversight. Furthermore, the quality of financial reporting is determined differently compared to firms in the services and manufacturing industry. Tools- We measure the quality of financial reporting using existing models in the literature. We use accruals-based models and real earnings management as an alternative measure. To estimate uncertainty, we rely on two important indexes, the Economic Sentiment Indicator and Business Confidence Indicator; additionally, we use another measure for robustness check. For accounting enforcement, we use the strength of auditing and accounting standards, and another measure grounded in the literature for robustness check. Findings- Our results suggest that uncertainty is negatively associated with the financial reporting quality in the EU. This indicates that uncertainty worsens the financial reporting quality. In addition, we investigate the moderating role of accounting enforcement. We find that when accounting enforcement increases by one unit, the negative association between financial reporting quality and uncertainty decreases between 2.7% and 4.5%. Our results are consistent and robust to the use of alternative measures for financial reporting quality, uncertainty, and accounting enforcement. Contribution- This study contributes to literature in several ways. The EU presents a particular context that allows us to investigate more thoroughly the association between financial reporting quality and uncertainty using cross country sample. Furthermore, this study provides relevant insights to the policymakers specific to EU institutional settings. Research at EU level is welcome as previous analysis is limited to only seven EU countries. Therefore, more evidence is needed to form solid conclusions relevant for the EU. Additionally, we provide strong evidence about the moderating role of accounting enforcement, which was not investigated in literature in the context of uncertainty. Our results are significant for the EU, since the last years were characterized by high uncertainty, and considering the current developments, the next years will also be under the sign of uncertainty. The findings provide useful information to interested parties on the association between uncertainty and financial reporting quality and highlight the importance of accounting enforcement.
Keywords: M41; M42; M48; 650; financial reporting; uncertainty; accounting enforcement